Ritual Rukat’tu sebagai Ruang Liminalitas dalam Perjumpaan Agama Kristen dan Jingitiu di Sabu Barat - Lukas, Alma Victoria Anastasia; Lattu, Izak Y. M.; Tampake, Tony; Ludji, Irene (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Interfaith encounters and dialogue in Indonesia have always focused only on official religions recognized by the Indonesian government. The purpose of this research is to further examine the encounter between official religions in Indonesia, specifically Protestant Christianity and the indigenous religion (ancestral religion) in West Sabu. The people of Sabu have an indigenous religion called Jingitiu. The encounter between Christianity and Jingitiu occurs in the rukat'tu ritual as a liminal space and the creation of social recognition of Jingitiu. The research method used is qualitative with a critical ethnographic approach. The theory used with an interdisciplinary approach is liminality according to Victor Turner and social recognition according to Axel Honneth. The findings show that discrimination, differentiation and public rejection are still ongoing to this day, but the rukat'tu ritual becomes a space of acceptance between Christianity and indigenous religions by sitting on one mat together in performing rituals, eating traditional food together and supporting each other in times of sorrow. This can foster a sense of brotherhood, equality, peace and harmonious relationships between religions.